Fasting blood glucose and risk of Stroke: A Dose–Response meta-analysis. Issue 5 (May 2021) - Shi, Han; Ge, Yusong; Wang, Hongming; Zhang, Yun; Teng, Weiyu; Tian, Li
Summary: Background & purpose: A growing number of studies have shown that fasting blood glucose is related to the risk of stroke, however, the dose–response association between fasting blood glucose and the risk of stroke is still unclear. Accordingly, we conducted a dose–response meta-analysis to evaluate the relationship between fasting blood glucose and the risk of stroke by summarizing cohort studies. Methods: PubMed and Embase databases were searched for related studies (until October 2020). Cohort studies examining the influence of fasting blood glucose on stroke risk were summarized. A dose–response relationship was determined using a random-effect model. Results: Eighteen cohort studies involving 2, 555, 666 participants were included. The pooled relative risk for the high-versus-low categories was 1.79 (95% CI: 1.68–1.91) in all people, and 1.16 (95% CI: 1.11–1.21) in non-diabetic people. In addition, there was a non-linear relationship between fasting blood glucose and stroke risk. The incidence of stroke was reduced to its lowest point when fasting blood glucose level was 70–100 mg/dL. Conclusion: Fasting blood glucose was positively related to stroke risk, with a non-linear dose–response relationship.